2014
DOI: 10.1097/qai.0000000000000081
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to HIV Care and Antiretroviral Therapy by HIV Testing Service Type in Central Mozambique

Abstract: Background Access to ART has increased dramatically in resource-limited settings since its introduction a decade ago. However, ART coverage remains low in countries with the highest disease burden, which may be partially explained by poor testing to care linkages. HIV testing service may impact early attrition in the HIV treatment cascade. Methods A retrospective cohort study was conducted in 18 clinics in central Mozambique using routine patient data and monthly reports. Patients referred from voluntary cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
3
15
1
Order By: Relevance
“…Retention rates in this cohort after 6 and 12 months were similar to some other studies [16], but higher than in the majority of comparable investigations: Peltzer et al, or Fox and Rosen found an all-cause attrition rate double as high in their South African cohorts [18,24]. According to UNAIDS, there is considerable variation in reported retention rates among countries, but data from 18 countries showed that 12-month retention rates averaged 86% [1], similar to the rate found in our Ugandan cohort.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Retention rates in this cohort after 6 and 12 months were similar to some other studies [16], but higher than in the majority of comparable investigations: Peltzer et al, or Fox and Rosen found an all-cause attrition rate double as high in their South African cohorts [18,24]. According to UNAIDS, there is considerable variation in reported retention rates among countries, but data from 18 countries showed that 12-month retention rates averaged 86% [1], similar to the rate found in our Ugandan cohort.…”
Section: Discussionsupporting
confidence: 91%
“…This has also been discussed as an explanation for women enrolling into ART services at earlier disease stages than men, as frequently described in previous studies [10,11,16]. Generally, in low-and middleincome countries, one in four people who initiate ART present at late disease stage with CD4-cell counts below 100 cells/mm³ [1].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…23 In 2013, the Ministry of Health (MOH) began its national rollout of Option B+ services to streamline PMTCT services and increase ART coverage. 24 Maternal and child health (MCH) nurses were trained to manage ART through the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Poor links with ongoing care is a challenge in many settings [8], especially when the mother is reluctant to accept or disclose her HIV diagnosis [9]. However, it is imperative that systems are put in place to retain HIV-exposed babies in care, to optimize PMTCT efforts and to initiate ART as early as possible in the event that the baby becomes HIV infected [10].…”
Section: Discussionmentioning
confidence: 99%